If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x/3)+(5/3)=(7x/5)-(2/5)
We move all terms to the left:
(x/3)+(5/3)-((7x/5)-(2/5))=0
We can not solve this equation
| 6x+1=-38-5x | | 8x–2(4)=48, | | x/(-2)+17=12 | | 12x+2=13+x | | 9w^2+9w-54=11w+3 | | 2^3x+1×5^4x-2=110 | | 2^4x^-1=32 | | -18x+36=36-18x | | (y+4)−(y−1)=6y | | 625=5^-6x+^5 | | |5x-1|=|2x+5| | | 5^(3x-1)=49 | | 5^3x-1=49 | | 10.50x+3.75(82)=2071.50 | | 2x-1=9x+1 | | 19=6x/26 | | 28=6(x+3)-4x | | 6b+7=325 | | 0.06y=1.8 | | X/2+17=5x/8+4-x | | 2x+17=5x/8+4-x | | 7x+2-3x=14 | | X/2+5x/8=21-x | | 2x/5+3x/5=8+3 | | 8x-5-2x=25 | | 3n+9=5n-7 | | 7+4x(4-1)=19 | | 2x-4+9x=40 | | ─9r+4r─11+2=3r+7─8r+9 | | 32(40-4.5x)=16(4x-7)+60.8 | | 3(m-2)-2=4(m-4) | | 7(x-2)=-3(x+3)+33 |